2019
DOI: 10.1038/s41467-019-10046-x
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the HIV-infected brain to improve ischemic stroke outcome

Abstract: HIV-associated cerebrovascular events remain highly prevalent even in the current era of antiretroviral therapy (ART). We hypothesize that low-level HIV replication and associated inflammation endure despite antiretroviral treatment and affect ischemic stroke severity and outcomes. Using the EcoHIV infection model and the middle cerebral artery occlusion as the ischemic stroke model in mice, we present in vivo analysis of the relationship between HIV and stroke outcome. EcoHIV infection increases infarct size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 98 publications
2
53
0
Order By: Relevance
“…ECV protein concentration was measured by BCA protein assay kit (Pierce). Equal amount of proteins (8)(9)(10)(11)(12)(13)(14)(15)(16) μg/lane) was loaded on sodium dodecyl sulfate polyacrylamide 4-20% ready gels (BioRad, Hercules, CA) and electrotransferred to a nitrocellulose membrane using a transfer pack system (BioRad). The blots were probed at 4°C with rabbit anti-ASC antibody (Catalog # AL177, Adipogen Life Sciences, San Diego, CA), rabbit anti-NLRP3 antibody (Catalog # LSB4321, LSBio, Seattle, WA) or mouse anticaspase-1 antibody (Catalog # sc-514, Santa Cruz Biotechnology Inc) (1:400) in 5% milk-TBS-T. After washing 3 times with TBS-T, the samples were incubated with secondary antibodies diluted at 1:20,000 (anti-mouse 800CW or anti-rabbit 680RD).…”
Section: Protein Isolation and Western Blotmentioning
confidence: 99%
“…ECV protein concentration was measured by BCA protein assay kit (Pierce). Equal amount of proteins (8)(9)(10)(11)(12)(13)(14)(15)(16) μg/lane) was loaded on sodium dodecyl sulfate polyacrylamide 4-20% ready gels (BioRad, Hercules, CA) and electrotransferred to a nitrocellulose membrane using a transfer pack system (BioRad). The blots were probed at 4°C with rabbit anti-ASC antibody (Catalog # AL177, Adipogen Life Sciences, San Diego, CA), rabbit anti-NLRP3 antibody (Catalog # LSB4321, LSBio, Seattle, WA) or mouse anticaspase-1 antibody (Catalog # sc-514, Santa Cruz Biotechnology Inc) (1:400) in 5% milk-TBS-T. After washing 3 times with TBS-T, the samples were incubated with secondary antibodies diluted at 1:20,000 (anti-mouse 800CW or anti-rabbit 680RD).…”
Section: Protein Isolation and Western Blotmentioning
confidence: 99%
“…In addition to aforementioned viral factors, elevated levels of ROS and increased circulating levels of proinflammatory molecules, such as TNF-α, IL-1β, and C-reactive protein, can contribute to underlying chronic inflammation in infected individuals (Brabers and Nottet 2006;Ross et al 2009;Younas et al 2016). These changes are accompanied by an increase in adhesion molecules on the brain endothelium, such as VCAM-1, ICAM-1, P-selecting, and platelet endothelial cell adhesion molecule (PECAM-1 or CD31) (Dhawan et al 1997;Wolf et al 2002;Bertrand et al 2019b). The accumulation of these inflammatory mediators can further lead to the development on vasculopathies associated with HIV infection (Chetty 2001).…”
Section: Status Of Bbb In Hiv Infected Patientsmentioning
confidence: 99%
“…Experimental studies also demonstrated that Efavirenz can have deleterious effects on ischemic stroke, leading to increased tissue damage and BBB deterioration (Bertrand et al 2016b). On the other hand, administration of low toxicity ART is beneficial for the outcome of stroke when compared to the untreated HIVinfected group (Bertrand et al 2019b). An additional factor to take into consideration is that co-morbidities can be exacerbated by ART toxicity.…”
Section: Art-induced Bbb Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aβ deposition occurs mostly in the perivascular space [3,[7][8][9], which points to the brain microvessels having a role in amyloid pathology. In support of this notion, the blood-brain barrier (BBB), a critical player in the brain infection by HIV and the development of HIV-associated cerebrovascular comorbidities [10,11], was postulated to regulate Aβ homeostasis as an interface contributing to Aβ accumulation in the brain [12]. Indeed, it was demonstrated that the receptor for advanced glycation end products (RAGE) can mediate Aβ transport across the BBB and accumulation in the brain [13].…”
Section: Introductionmentioning
confidence: 99%